Molecular characterization of type I IFN-induced cytotoxicity in bladder cancer cells reveals biomarkers of resistance - Jennifer L. Green (Elsevier, 2021)
Although anti-tumor activities of type I interferons (IFNs) have been recognized for decades, the molecular mechanisms contributing to clinical response remain poorly understood. The complex functions of these pleiotropic cytokines include stimulation of innate and adaptive immune responses against tumors as well as direct inhibition of tumor cells. In high-grade, Bacillus Calmette-Guérin (BCG)-unresponsive non-muscle-invasive bladder cancer, nadofaragene firadenovec, a non-replicating adenovirus administered locally to express the IFNα2b transgene, embodies a novel approach to deploy the therapeutic activity of type I IFNs while minimizing systemic toxicities. Deciphering which functions of type I IFN are required for clinical activity will bolster efforts to maximize the efficacy of nadofaragene firadenovec and other type I IFN-based therapies, and inform strategies to address resistance. As such, we characterized the phenotypic and molecular response of human bladder cancer cell lines to IFNα delivered in multiple contexts, including adenoviral delivery. We found that constitutive activation of the type I IFN signaling pathway is a biomarker for resistance to both transcriptional response and direct cytotoxic effects of IFNα. We present several genes that discriminate between sensitive and resistant tumor cells, suggesting they should be explored for utility as biomarkers in future clinical trials of type I IFN-based anti-tumor therapies.